Passive Immunization Hesitancy Among Rabies-Exposed Individuals in China: A Multicenter Cross-Sectional Study - Qisheng Hou; Xiaoliang Xu; Si Liu; Chen Sun; Fengfeng Zhu; Yang Yang; Jianchao Shao; Yifan Wang; Yanqiang Feng; Yingxiang Liu; Yan Yan; Song Wang; et al. (Tropical Medicine and Infectious Disease, 2026)
Background: Rabies is an almost universally fatal disease for which post-exposure prophylaxis (PEP), including passive immunization (PI) with rabies immunoglobulin or monoclonal antibodies, remains the only effective intervention. Despite established clinical guidelines, real-world PI utilization remains suboptimal. This study aimed to investigate the prevalence and determinants of PI hesitancy among previously unvaccinated patients with Category III rabies exposure in China. Methods: This multicenter cross-sectional questionnaire study was conducted at 12 rabies PEP clinics or emergency departments in 12 provinces of mainland China. The analysis included 585 previously unvaccinated adults with Category III rabies exposure who initially hesitated to receive or declined PI. The questionnaire collected sociodemographic characteristics, exposure profiles, awareness of the early protection gap, reasons for initial PI hesitancy or refusal, the decision to receive PI during the same clinical encounter, and PI product selection. Multivariable logistic regression identified factors associated with PI treatment decisions, with results reported as adjusted odds ratios (aORs); reason-specific models used the Benjamini–Hochberg false discovery rate correction. All inferential analyses were restricted to adults. Results: Among 5068 eligible previously unvaccinated patients with Category III rabies exposure, 2866 (57%) initially hesitated to receive or declined recommended PI. Of 617 questionnaire respondents, 32 minors were excluded, leaving 585 adults for all inferential analyses. The leading reasons for initial hesitancy were lack of understanding of the immediate protective role of PI (199/585, 34%), belief that vaccination alone was sufficient (194/585, 33%), and high cost (178/585, 30%). During the same clinical encounter, 320/585 adults (55%) chose to receive PI. Awareness of the early protection gap (aOR 2.63, 95% CI 1.75–3.98, p < 0.001) and bachelor’s degree or higher (aOR 1.61, 95% CI 1.07–2.43, p = 0.023) were positively associated with the decision to receive PI, whereas head/face wounds were negatively associated (aOR 0.53, 95% CI 0.30–0.92, p = 0.026). In reason-specific models, lack of knowledge about immediate protection was associated with higher odds of choosing PI (aOR 2.43, 95% CI 1.62–3.68, BH-FDR p < 0.001), whereas high cost was associated with lower odds (aOR 0.41, 95% CI 0.27–0.62, BH-FDR p < 0.001). Conclusion: Hesitancy toward and refusal of PI were observed among previously unvaccinated adults with Category III rabies exposure, yet initial hesitation or refusal is not irreversible. Early protection gap awareness was positively associated with PI choice, whereas cost-related concern was negatively associated. Clear explanation of protection timing and attention to cost-related barriers may support informed PI treatment decisions.